Desenvolvimento do sorgo CV. BRS Ponta Negra irrigado com água salobra e submetido a diferentes doses de esterco bovino e biofertilizantes - Sousa, Robson Alexsandro de (2015)
This study aimed to evaluate the effects of salinity of irrigation water and organic compound on the development in sorghum [Sorghum bicolor (L.) Moench.] cv. BRS Ponta Negra. Therefore, three experiments were performed: the first, there was the effect of cattle manure and commercial biofertilizer Ative® and irrigation with different salinity water in the sorghum plants; in the second there was the cattle manure doses (10, 20, 30 and 40 t ha-1) and the salinity of the irrigation water; and in the third, there was the use of liquid biofertilizer Ative® doses (75, 150, 225 and 300 L ha-1 ) and salinity irrigation water. The plants were grown in pots containing 23 kg of sandy soil under greenhouse conditions. Salinity levels were 0.2; 2.0; 4.0; and 6.0 dS m-1, being used for its preparation is pond water with NaCl added in the first experiment; the second and third experiments with NaCl salts, CaCl22H2O and MgCl26H2O , the ratio of 7:2:1. The experimental design was completely randomized with five replicates in a factorial 4 x 3 in the first experiment; four replications, in a factorial 4 x 4, second and third experiments. The following variables were assessed: total dry matter; culms + sheath diameter; plant height; total leaf area; leaf succulence; bulk density leaf; sodium, potassium, chloride, calcium, magnesium and phosphorus in the leaves and culms + sheath of plants; proline and carbohydrates in the leaves of plants. In addition to the soil analysis of the experiments. The results show the three experiments that salinity affected all variables, with beneficial cattle manure and biofertilizer, however, without reducing the deleterious effects of salts when applied through irrigation water.